Use of antimicrobial seal in central venous catheter in hemodialysis patients - Matos, Douglas Nuernberg de; Leyraud, Samantha Zamberlan (Seven Editora, 2023)
Antibiotic lock therapy is an adjunctive therapy used in the treatment of bloodstream infections related to central venous catheters for hemodialysis and consists of the use of high concentrations of ATB to close the lumens between hemodialysis sessions.The central venous catheter is the least desirable form of vascular access due to its 2- to 3-fold increased risk of morbidity and mortality. Procedures to maintain vascular access can result in inefficient treatments and recurrent hospital admissions, and are constantly a major problem for the healthcare system.Contamination of the external and internal surface of the central venous catheter by the extraluminal and intraluminal routes, respectively, involves the transfer of microorganisms during manipulation of the central venous catheter, as well as during dressing changes or central venous catheter connection and disconnection.The purpose of the antimicrobial seal is to prevent colonization and biofilm formation, for which an antimicrobial agent is required. An anticoagulant is needed to prevent catheter dysfunction. This intervention can also be an adjunct to systemic antibiotic therapy and consists of rescuing the catheter by instilling the solution into each lumen of the catheter at the end of each dialysis session for the same duration of systemic therapy, when there is an ongoing bloodstream infection (BSI). DOI:https://doi.org/10.56238/sevened2023.004-037